KEBERADAAN MADRASAH DINIYAH TAKMILIYAH USHULUDDIN, DALAM PEMBINAAN ANAK-ANAK DI DESA KURANJI KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Agus Supian; Najib Amrullah (Program Studi PGMI STAI Al Falah Banjarbaru, 2018)
This study discusses the existence of Madrasah Diniyah Takmiliyah Usul, which covers the development and role of madrasah diniyah factor as well as against religious coaching in coaching children at Kuranji village sub-district of Landasan Ulin Banjarbaru. Formulation of the problem in this thesis is, how the development and role of Madrasah Diniyah Takmiliyah education Usbuluddin in the construction of religion of children, and the factors that encourage the education of Madrasah Diniyah Takmiliyah Usbuluddin in constructor Islamic kids at Kuranji Subdistrict. Landasan Ulin Banjarbaru. Based on the formulation of the problem, then this research aims to know the existence of Madrasah Diniyah Takmiliyah Usul, which includes concept development and the role of the madrasah diniyah factor as well as against religious coaching in coaching children in Jl. Kuranji Subdistrict Landasan Ulin Banjarbaru. The subject in this study is the community and alumni of Madrasah Diniyah Takmiliyah Usul. The object in this research is the existence of Madrasah Diniyah Takmiliyah Usul in the construction of Islamic children in JI. Kuranji Subdistrict Landasan Ulin Banjarbaru. Data collection techniques in research are through interview, observation, and data processing, engineering documentation in this research is with the editing and interpretation of the data. As for analyzing data, the qualitative descriptive analysis used and draw conclusions using inductive techniques. Based on the research of basil it is known that the presence of Madrasah Diniyah Takmiliyah Usul in the construction of religion for children is generally done well. This is driven by several factors, namely teachers ' factors, environmental factors, factors of students and allocation of time available. Key Words: Coaching Children, Madrasah Diniyah, The Religion of Islam